Cytosolic detection of phagosomal bacteria—Mechanisms underlying PAMP exodus from the phagosome into the cytosol - Ragland, Stephanie A.; Kagan, Jonathan C. (Molecular microbiology, 2021)
The metazoan innate immune system senses bacterial infections by detecting highly conserved bacterial molecules, termed pathogen‐associated molecular patterns (PAMPs). PAMPs are detected by a variety of host pattern recognition receptors (PRRs), whose function is to coordinate downstream immune responses. PRR activities are, in part, regulated by their subcellular localizations. Accordingly, professional phagocytes can detect extracellular bacteria and their PAMPs via plasma membrane‐oriented PRRs. Conversely, phagocytosed bacteria and their PAMPs are detected by transmembrane PRRs oriented toward the phagosomal lumen. Even though PAMPs are unable to passively diffuse across membranes, phagocytosed bacteria are also detected by PRRs localized within the host cell cytosol. This phenomenon is explained by phagocytosis of bacteria that specialize in phagosomal escape and cytosolic residence. Contrary to this cytosolic lifestyle, most bacteria studied to date spend their entire intracellular lifestyle contained within phagosomes, yet they also stimulate cytosolic PRRs. Herein, we will review our current understanding of how phagosomal PAMPs become accessible to cytosolic PRRs, as well as highlight knowledge gaps that should inspire future investigations. The graphical illustrates the several means by which bacterial products may exit phagosomes to stimulate innate immune receptors present in the cytoplasm of eukaryotic cells. Each of these means of pathogen‐associated molecular pattern exodus is discussed in this review.